2018
DOI: 10.3390/cosmetics5040061
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruption by Mixtures in Topical Consumer Products

Abstract: Endocrine disruption has been gathering increasing attention in the past 25 years as a possible new threat for health and safety. Exposure to endocrine disruptor has been progressively linked with a growing number of increasing disease in the human population. The mechanics through which endocrine disruptors act are not yet completely clear, however a number of pathways have been identified. A key concern is the cumulative and synergic effects that endocrine disruptors could have when mixed in consumer product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 132 publications
(171 reference statements)
0
7
0
Order By: Relevance
“…Caliman F. and Gavrilescu M. (2009) indicated that synthetic organic chemicals for hygienic as well as some medications such as contraceptives, antibiotics, β-blockers, and analgesics areED agents [17].The reports from other authors show EDC in pharmaceutical and personal care products [18,19].A number of substances that are included in hygiene products, cosmetics, perfumesand medicaments are listed as EDC [20,21]. Ripamonti and co-authors (2018) mentioned ethynilestradiol (used in contraceptive pills), parabens, formaldehyde, glutaraldehyde, aromatic amine derivatives, metal salts, UV filters, phthalates, solvents, fragrance ingredients and more [22]. It is true that there is still lack of information about the direct connection between EDC and skin conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Caliman F. and Gavrilescu M. (2009) indicated that synthetic organic chemicals for hygienic as well as some medications such as contraceptives, antibiotics, β-blockers, and analgesics areED agents [17].The reports from other authors show EDC in pharmaceutical and personal care products [18,19].A number of substances that are included in hygiene products, cosmetics, perfumesand medicaments are listed as EDC [20,21]. Ripamonti and co-authors (2018) mentioned ethynilestradiol (used in contraceptive pills), parabens, formaldehyde, glutaraldehyde, aromatic amine derivatives, metal salts, UV filters, phthalates, solvents, fragrance ingredients and more [22]. It is true that there is still lack of information about the direct connection between EDC and skin conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Fatoki et al (2018) corroborated the fact that livestock is a source of oestrogen in the environment. Octylphenol is used in the manufacture of detergents, (Ripamonti et al 2018). This might be the reason for its presence in the wastewaters influents.…”
Section: Discussionmentioning
confidence: 99%
“…• For a decade, Environmental Working Group (EWG) has worked to raise concerns about sunscreens with oxybenzone, which is found in nearly all Americans, detected in breast milk and potentially causing endocrine disruption [43].…”
Section: Sunburn and Sunscreen Factsmentioning
confidence: 99%